'That decision really was mine…'. Insider perspectives on health care controversies about intersex/diverse sex development. Issue 4 (1st April 2021) - Lampalzer, Ute; Briken, Peer; Schweizer, Katinka
Abstract: After 20 years of debate on intersex care, there has been a slight movement away from the paradigm of 'optimal gender' including early genital modification to conform to predicted gender identity towards a paradigm of 'full consent' including the provision of full information about the risks, benefits and alternatives to interventions and the postponement of irreversible interventions on minors too young to give informed consent. However, controversy continues. Against this background, the aim of this study was to analyse core aspects of current debates in intersex care. Focus was placed on controversies about surgery on external genitalia; gonadectomies; the expressed wishes of patients under the age of consent; and how to deal with intersex within the family. Eight guideline-based interviews were conducted with two people with intersex/diverse sex development conditions who had been subjected to surgery, two parents of children with an intersex/dsd condition, two medical doctors, and two psychologists. Data were analysed thematically. Findings indicate that while 'full consent' influenced actions and debate, the persons involved held differing opinions about how this policy can or should be achieved. In addition, the data illustrated how concepts such as normalcy, identity and sexuality are relevant when dealing with intersex issues.